Differential Degradation of Nonylphenol Isomers by Sphingomonas xenophaga Bayram - Gabriel, Frédéric L. P. (American Society for Microbiology, 2005)
Sphingomonas xenophaga Bayram, isolated from the activated sludge of a municipal wastewater treatment plant, was able to utilize 4-(1-ethyl-1,4-dimethylpentyl)phenol, one of the main isomers of technical nonylphenol mixtures, as a sole carbon and energy source. The isolate degraded 1 mg of 4-(1-ethyl-1,4-dimethylpentyl)phenol/ml in minimal medium within 1 week. Growth experiments with five nonylphenol isomers showed that the three isomers with quaternary benzylic carbon atoms [(1,1,2,4-tetramethylpentyl)phenol, 4-(1-ethyl-1,4-dimethylpentyl)phenol, and 4-(1,1-dimethylheptyl)phenol] served as growth substrates, whereas the isomers containing one or two hydrogen atoms in the benzylic position [4-(1-methyloctyl)phenol and 4-n-nonylphenol] did not. However, when the isomers were incubated as a mixture, all were degraded to a certain degree. Differential degradation was clearly evident, as isomers with more highly branched alkyl side chains were degraded much faster than the others. Furthermore, the C(9) alcohols 2,3,5-trimethylhexan-2-ol, 3,6-dimethylheptan-3-ol, and 2-methyloctan-2-ol, derived from the three nonylphenol isomers with quaternary benzylic carbon atoms, were detected in the culture fluid by gas chromatography-mass spectrometry, but no analogous metabolites could be found originating from 4-(1-methyloctyl)phenol and 4-n-nonylphenol. We propose that 4-(1-methyloctyl)phenol and 4-n-nonylphenol were cometabolically transformed in the growth experiments with the mixture but that, unlike the other isomers, they did not participate in the reactions leading to the detachment of the alkyl moiety. This hypothesis was corroborated by the observed accumulation in the culture fluid of an as yet unidentified metabolite derived from 4-(1-methyloctyl)phenol.